2011
DOI: 10.1074/mcp.m110.002246
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR-presented Peptide Repertoires Derived From Human Monocyte-derived Dendritic Cells Pulsed With Blood Coagulation Factor VIII

Abstract: Activation of T-helper cells is dependent upon the appropriate presentation of antigen-derived peptides on MHC class II molecules expressed on antigen presenting cells.In the current study we explored the repertoire of peptides presented on MHC class II molecules on human monocyte derived dendritic cells (moDCs) from four HLA-typed healthy donors. MHC class II-bound peptides could be routinely recovered from small cultures containing 5 ؋ 10 6 cells. A fraction of the identified peptides were derived from prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 47 publications
4
83
0
Order By: Relevance
“…38 In addition, peptides with core sequence FRN-QASPRY (A3 domain; residues 1766-1786) are presented less efficiently in the presence of VWF. Interestingly, this peptide is presented by multiple MHC class II alleles 9,10 and has also been described as a functional T-cell epitope in humanized E17 HLA-DRB1*1501 mice. 39 These observations raise the possibility that VWF modulates CD4 + Tcell responses by affecting FVIII peptide presentation by antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…38 In addition, peptides with core sequence FRN-QASPRY (A3 domain; residues 1766-1786) are presented less efficiently in the presence of VWF. Interestingly, this peptide is presented by multiple MHC class II alleles 9,10 and has also been described as a functional T-cell epitope in humanized E17 HLA-DRB1*1501 mice. 39 These observations raise the possibility that VWF modulates CD4 + Tcell responses by affecting FVIII peptide presentation by antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…9 Several studies have shown that VWF reduces the uptake of FVIII by iDCs. 13,18 However, whether VWF affects the processing and presentation of FVIII-derived peptides on MHC class II has not been addressed.…”
Section: Vwf Modulates the Presentation Of Fviii Derived Peptides On mentioning
confidence: 99%
See 2 more Smart Citations
“…Mass Spectrometry Analysis-FVIII peptides were separated by reverse-phase chromatography and sprayed in a LTQ OrbitrapXL mass spectrometer (Thermo Fisher Scientific) essentially as described (35). During reverse-phase chromatography, we employed a 40-min gradient from 0 to 35% (v/v) acetonitrile with 0.05% (v/v) acetic acid.…”
Section: Methodsmentioning
confidence: 99%